Tetranuclear Cu(ii)-chiral complexes: synthesis, characterization and biological activity. Issue 42 (2nd August 2019) - Peewasan, Krisana; Merkel, Marcel P.; Zarschler, Kristof; Stephan, Holger; Anson, Christopher E.; Powell, Annie K.
Abstract : A pair of tetranuclear chiral Cu(ii )-Schiff-base complexes were synthesized using enantiomerically pure ( S )-H2 L and ( R )-H2 L ligands. These were characterised using single-crystal X-ray diffraction and CD spectroscopy and their biological activity tested. Abstract : Tetranuclear chiral Cu(ii )-Schiff-base complexesS-1 andR-1, were synthesised using enantiomerically pure ( S )-(H2 vanPheol) and ( R )-(H2 vanPheol) ligands respectively in the ratio of 1 : 1 of Cu(NO3 )2 to ( S / R )-(H2 vanPheol) in MeOH at room temperature. A pair of polynuclear chiral Cu(ii )-cluster complexes were characterized using single-crystal X-ray diffraction, elemental analysis, infrared and CD spectroscopy. The results revealed the importance of these chiral ligands encouraging the arrangement of copper metal in non-centrosymmetric polar packing. The potential of the novel [Cu4 ( S / R -vanPheol)2 ( S / R -HvanPheol)2 (CH3 OH)2 ](NO3 )2 complexes as biologically active compounds was assessed in particular regarding their anti-proliferative and anti-microbial properties.